2018
DOI: 10.4269/ajtmh.17-0454
|View full text |Cite
|
Sign up to set email alerts
|

Status of Insecticide Resistance in Papua New Guinea: An Update from Nation-Wide Monitoring of Anopheles Mosquitoes

Abstract: Insecticide resistance (IR) monitoring is an important component of vector-borne disease control. The last assessment of IR in Papua New Guinea (PNG) was conducted in 2010. Since then, vector populations have been exposed to higher levels of pyrethroids with the continued nation-wide distribution of insecticide-treated nets. Here, we provide an update on phenotypic IR in four highly malaria-endemic areas of PNG. IR against deltamethrin, lambda-cyhalothrin, and dichlorodiphenyltrichloroethane was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Extensive insecticide resistance monitoring using WHO-tube assays was conducted prior to, during and after this study and with larvae collected from the same habitats, confirming full susceptibility of these wild-caught mosquitoes to deltamethrin, lambda-cyhalothrin, DDT, Bendiocarb and Malathion insecticides. Overall, there is no indication of pyrethroid, and especially deltamethrin, resistance in Anopheline populations from anywhere in PNG 19 .…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Extensive insecticide resistance monitoring using WHO-tube assays was conducted prior to, during and after this study and with larvae collected from the same habitats, confirming full susceptibility of these wild-caught mosquitoes to deltamethrin, lambda-cyhalothrin, DDT, Bendiocarb and Malathion insecticides. Overall, there is no indication of pyrethroid, and especially deltamethrin, resistance in Anopheline populations from anywhere in PNG 19 .…”
Section: Methodsmentioning
confidence: 95%
“…with solar-powered lights) allows people to be active much longer into the night than previously, even in remote PNG communities, which may enhance human-vector contact further. While insecticide resistance will have a detrimental effect on LLIN bioefficacy 17 , 18 regular insecticide resistance monitoring activities show no signs of emerging pyrethroid resistance in the anopheline mosquito populations in PNG since the beginning of the LLIN distributions 19 . This stands in contrast to recently found high levels of pyrethroid resistance in Aedes aegypti populations in PNG 20 .…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the increase in resistance to pyrethroids over the past decade is due in part to the higher coverage of insecticide-based interventions, such as LLINs. However, studies have shown conflicting results with some reports of increasing resistance following bednet distributions [ 24 – 27 ], and other reports of no increases despite sustained insecticidal campaigns [ 28 – 30 ]. Although ascertaining the effect of bednet coverage was not a primary goal of this study, it was possible to investigate the impact of net use through cross-sectional surveys that were conducted concurrently to resistance measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes were reared to adult stage in a permanent (Madang) or temporary (Port Moresby) insectary. Bioassays were conducted as previously described [18] using WHO standard methodology, and limiting concentration filter papers obtained from School of Biological Sciences, Universiti Sains Malaysia, which is the regional centre manufacturing these commodities. Assays were always accompanied by at least one control of 20 mosquitoes (20 per cylinder).…”
Section: Methodsmentioning
confidence: 99%